Cardiovascular Disease and Mental Distress Among Ethnic Groups in Kyrgyzstan - Azfar, Hossain Syed; Dzhusupov, Kenesh O.; Orru, Hans; Nordin, Steven; Nordin, Maria; Orru, Kati (Frontiers in Public Health, 2021)
The purpose of this study was to characterize different ethnic groups in Kyrgyzstan regarding cardiovascular disease (CVD) and mental distress, and to investigate the association between CVD and mental distress. The mental distress was measured in terms of sleep disturbance, burnout, and stress. Materials and Methods: A cross-sectional study was carried out among six ethnic groups in Kyrgyzstan, aged 18 years and above. The sample was stratified for age, education, family status, and income. We used the Karolinska Sleep Questionnaire to assess sleep disturbance, the physical and emotional subscale of the Shirom Melamed Burnout Questionnaire to assess burnout, and the 10-item Perceived Stress Scale to assess perceived stress. Results: The distribution of CVD differed significantly between the six ethnic groups, with higher prevalence among East Europeans, and Western Asians and lower among Other minorities and Central Asians. In all ethnic groups in Kyrgyzstan, individuals with CVD had increased odds of sleep disturbance and burnout. There was a significant difference in burnout and stress between persons with and without CVD in Kyrgyz and East European ethnic groups. Conclusion: There was a significant difference in burnout and stress between persons with and without CVD in Kyrgyz and East European ethnic groups. In addition to CVD prevention, mitigating sleep disturbance and preventing burnout in the general population should be aimed at in public health measures.